Analisis strategi deferensiasi produk pada bank syariah untuk meningkatkan daya saing usaha mikro, kecil dan menengah (UMKM) di era digital - Afifa, Fania Eka Bella (Maliki Interdisciplinary Journal, 2025)
Micro, Small and Medium Enterprises in Indonesia face challenges from changes in the business environment and intense competition. Islamic banks play an important role in supporting Micro, Small, and Medium Enterprises through fairness and partnership-based financing, as well as providing technical and non-technical assistance to improve competitiveness. This study aims to analyze the product differentiation strategy of Islamic banks in supporting the growth of Micro, Small and Medium Enterprises in the digital era and identify the key success factors. Using a qualitative approach and comparative analysis, data were collected from interviews with practitioners and Micro, Small, and Medium Enterprises actors as well as policy documents. Innovative and quality product differentiation strategies can attract the attention of Micro, Small, and Medium Enterprises and improve service access through digital technology, strengthen branding, and increase the resilience of Micro, Small, and Medium Enterprises. Islamic bank support is expected to contribute to the sustainable growth of Micro, Small, and Medium Enterprises, create jobs, and strengthen the national economy.